An Analysis of Glutathionylation in the Modulation of the Critical Innate Immune Regulators Mal and NEK7 - HUGHES, MARK (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2018)
Macrophages are critical innate immune cells that sense pathogen associated molecular patterns (PAMPs) and host-derived damage associated molecular patterns (DAMPs) through specialized Toll-like receptors (TLRs) to maintain homeostasis. TLR activation drives production of anti-microbial reactive oxygen species (ROS), which bombards invading microbes and must therefore be highly regulated. Overproduction of ROS causes oxidative imbalance, which can be sensed by redox sensitive protein machinery. The main sensor of oxidative insult is the thiol group on cysteine amino acids, which are amenable to redox-induced post-translational modification. Glutathione (GSH), the most abundant cellular antioxidant, regulates ROS levels and directly prevents oxidation of proteins by protecting redox sensitive thiol groups on cysteine amino acids. It is becoming more apparent that GSH not only contributes to cellular integrity, but rather alters protein function by reversibly modifying reactive cysteines. In this project, I sought to explore the role of GSH in TLR signalling. I focused on the TLR signalling adaptor MyD88-adaptor-like (Mal). The crystal structure of Mal revealed two cysteines, C91 and C157, that crystallised bound to a dithiothreitol (DTT) molecule. The cytosol of the cell is a reducing environment, thereby making these two cysteine residues very interesting potential post-translationally modified targets. Site-directed mutagenesis of C91 and C157 to alanine (C91A, C157A), identified that C91, and not C157, in Mal requires glutathionylation to drive TLR signalling. C91A was unable to interact with MyD88 or IRAK4. C91A also displayed diminished phosphorylation, known to be important for Mal function. Furthermore, positively charged amino acids adjacent to cysteines promote deprotonation of cysteine thiol groups, rendering them more sensitive to glutathionylation. Preventing glutathionylation of C91 by mutation of the positively charged flanking amino acid histidine to proline (H92P) mimicked the effect of C91A. Both C91A Mal and H92P Mal acted as dominant negative inhibitors of TLR4 signalling and were unable to reconstitute TLR4 signalling in Mal-deficient macrophages. Finally, LPS transiently increased the glutathionylation of Mal. Protein regulation by glutathionylation requires enzymes which can also deglutathionylate substrates as a regulatory mechanism. I also explored the redox enzyme Glutathione transferase omega 1 (GSTO1-1), which has deglutathionylating activity in TLR4 signalling. Using macrophages deficient in GSTO1-1, I identified novel roles for GSTO1-1 in the immunometabolic response to TLR4 activation. I demonstrate that GSTO1-1-deficient macrophages are highly glycolytic, and furthermore that GSTO1-1 deficiency drives production of the pro-inflammatory cytokine interleukin-1 (IL-1). Furthermore, using a novel covalent inhibitor of the active site of GSTO1-1 termed C1-27, I identify a role for GSTO1-1 in the regulation of pro-IL-1 processing by the NLRP3 inflammasome, acting via NEK7, and in the induction of Caspase-11, which mediates LPS lethality in vivo. I have found that the key NLRP3 regulator NEK7 is glutathionylated on cysteine 79 and cysteine 253 and provide evidence that GSTO1-1 is targeting NEK7 to promote NLRP3 activation. GSTO1-1 therefore also appears to play a role in NLRP3 inflammasome activation. Overall, this study identifies an important positive role for Mal glutathionylation, a negative role for the deglutathionylating enzyme GSTO1-1 in TLR4 signalling and a regulatory role for GSTO1-1 during inflammasome activation and Caspase-11 induction, highlighting the importance of glutathionylation as a regulator of macrophage activation.
APPROVED
Keywords: Macrophage; TLR; Glutathione; Mal/TIRAP; GSTO1-1; NEK7; Inflammasome; NLRP3